The Volunteer Missionary Educator in a Zambian Village - Maribel M. Chavez; Zosima A. Paňares; Emma A. Yaun; Lorlaine R. Dacanay; Aileen Basiga-Catacutan (Journal of Sociological Research, 2024)
The purpose of this study is to discover and narrate our experience as a volunteer missionary educator on the process of acculturation that have helped the Women Villagers (WV). This described the learning strategies, integration in the new culture, and poverty alleviation. Women’s empowerment has been advocated as a way not only to reduce poverty risk but also a way to improve a woman’s overall well-being. To be able to draw conclusions about the women’s learning strategies and what has made them work, We have looked at the experiences of five selected informants whose experiences successfully acculturated. The study employed a qualitative methodology, where information has been collected through semi-structured interviews, which were interpreted and analyzed using the study adopted from Spradley. The key findings were acculturation through education, specifically through projects and programs implemented. The goal was to teach outsiders about culture through both personal and empirical and help people within their culture better understand themselves. Done in an ethnographic way, an ethnographer “depicts people struggling to overcome adversity” and shows “people in the process of figuring out what to do, how to live, and the meaning of their struggles” (to borrow a phrase of Bochner and Ellis (2006). These findings can be put into practice to form better strategies and actions steps in organizational programs, school linkages or any Non-Government Organization. This can also be brought to the knowledge of any educators or missionary volunteers looking to successfully integrate, to make them aware of how their choices and goals, even those apparently unrelated, can impact the outcome of their integrated efforts.